2021
DOI: 10.3390/microorganisms9051034
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach to Study Glycosidase Activities from Bifidobacterium

Abstract: This study aimed to recover metagenome-assembled genomes (MAGs) from human fecal samples to characterize the glycosidase profiles of Bifidobacterium species exposed to different prebiotic oligosaccharides (galacto-oligosaccharides, fructo-oligosaccharides and human milk oligosaccharides, HMOs) as well as high-fiber diets. A total of 1806 MAGs were recovered from 487 infant and adult metagenomes. Unsupervised and supervised classification of glycosidases codified in MAGs using machine-learning algorithms allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…MAGs were recovered according to the method described by Sabater et al [9], using validated workflows for metagenome assembly and taxonomic classification [5]. These computational pipelines were used to process metagenomes from patients with CD and healthy individuals to further compare their metabolic activities (Figure 1).…”
Section: Metagenome Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…MAGs were recovered according to the method described by Sabater et al [9], using validated workflows for metagenome assembly and taxonomic classification [5]. These computational pipelines were used to process metagenomes from patients with CD and healthy individuals to further compare their metabolic activities (Figure 1).…”
Section: Metagenome Assemblymentioning
confidence: 99%
“…Genome annotation of MAGs can be used to study specific enzymatic activities such as those involved in carbohydrate metabolism [9]. Furthermore, MAGs could be used to build advanced genome-scale metabolic networks.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other bifidobacterial species, B. bifidum has a complete set of extracellular GHs, including α-sialidase, α-fucosidase, N-Acetylβ-hexosaminidase, β-galactosidase, and LNBase, to assimilate complex HMOs and leave degradation products, such as lactose, fucose, and sialic acid, outside the cell 45,[64][65][66] . Nishiyama et al 67 identified a sialidase (SiaBb2) involved in the degradation of HMOs and mucin and may promote the adhesion and colonization of B. bifidum on the surface of the intestinal mucosa.…”
Section: B Bifidum Extracellularly Degrade Hmos and Mucin O-sugarsmentioning
confidence: 99%
“…Once protein functional domains were annotated, those having Pfam entries that may correspond to bacterial MDRs described in the Transporter Classification Database (TCDB) database [19], were selected for comparative analysis. Furthermore, the distribution of these MDR functional domains in bile samples was compared to the one observed in 40 intestinal metagenomes sequenced by Kovatcheva-Datchary et al [20], which were pre-assembled in a previous work [21], and were introduced as inputs in this pipeline.…”
Section: Functional Analysis Of Bile Metagenome: Antibiotic and Multidrug Resistance Genes (Args And Mdrs)mentioning
confidence: 99%
“…One two-domain protein structure was also determined although its specific function could not be fully elucidated by remote homology. The distribution of these functional domains in bile samples was compared to the one observed in 40 faecal metagenomes from healthy individuals [20], which were pre-assembled in a previous study [21]. As it can be observed in Table 1, most metagenomic dark matter functional domains were identified in sequence from the H-04 sample and the fosmid library, while no functional domains could be determined in H-06 probably due in part to the low number of filtered reads obtained from this sample and the higher percentage of previously assigned sequences [1].…”
Section: Functional Analysis Of Bile Metagenome: Metagenomic Dark Mattermentioning
confidence: 99%